Performance of the EULAR Systemic sclerosis Impact of Disease (ScleroID) questionnaire as a patient-reported outcome measure for patients with diffuse systemic sclerosis - Ulf Mueller-Ladner; Marco Matucci-Cerinic; Yannick Allanore; Oliver Distler; Cosimo Bruni; Otylia Kowal-Bielecka; Kim Fligelstone; Roger Hesselstrand; László Czirják; Carina Mihai; Gunnel Sandqvist; Rucsandra Dobrota; et al. (RMD Open)
Objective Systemic sclerosis Impact of Disease (ScleroID) is the first comprehensive patient-reported outcome measure (PROM) specifically developed for systemic sclerosis (SSc). We investigated the performance of ScleroID in patients with diffuse cutaneous SSc (dcSSc), as a prerequisite for its use in randomised controlled trials (RCTs) testing potentially disease-modifying drugs.Methods All patients with dcSSc from the large, multicentric, ScleroID cohort were included. SSc-Health Assessment Questionnaire (HAQ), EuroQol-5 Dimensions and 36-item Short Form Health Survey (SF-36) were used as comparators. The study includes a longitudinal arm with a reliability visit at 7±3 days and a 12 months follow-up visit. The performance of ScleroID in dcSSc was assessed according to the Outcome Measures in Rheumatology filter.Results In total, 152 dcSSc patients were analysed (29% male, median age 54 years). ScleroID reflected well the disease impact of dcSSc, showing a good construct validity with high Spearman’s correlation coefficients with comparators (SSc-HAQ, 0.79, 95% CI (0.69, 0.86); HAQ-Disability Index, 0.72 95% CI (0.60, 0.80); SF-36 physical score, −0.69 95% CI (−0.77, –0.60)). The internal consistency was strong (Cronbach’s alpha 0.87, split-half reliability coefficient 0.88).In the longitudinal arm, 44 patients had a reliability visit and 113 had a follow-up visit, of whom 19/113 (17%) reported a significant change (11 improved, 8 worsened). ScleroID showed a good consistency and discriminative ability with excellent test–retest reliability (intraclass correlation coefficient 0.89, 95% CI (0.84, 0.92)) and moderate sensitivity to change (standardised response mean −0.63 in the improved subgroup and 0.48 in the worsened subgroup), but superior to the comparators.Conclusion The European Alliance of Associations for Rheumatology (EULAR) ScleroID performs well for patients with dcSSc. This supports its inclusion and regular assessment as PROM in RCTs.